Regulating the d-band center of Ru/CoMoO4 ternary heterostructure by interface engineering for accelerated hydrogen adsorption kinetics - Miao Ma; Min Yang; Cai-Yue Zhang; Hai-Yi Sun; Rong-Jing Su; Xiao-Rui Yue; Chen-Xi Li; Yong-Ming Chai; Bin Dong (Fuel, 2026)

Microalgae-based bioremediation of reverse osmosis concentrate (ROC): Mechanisms, techno-economic bottlenecks, and circular bioeconomy perspectives - Na-Hui Hao; Jun Li; Ya-Rong Qi; Zhuo Chen; Yu-Ming Wang; Yu-Jia Gao; Xu-Cheng Cai; Yu Hong; Hong-Ying Hu; Yin-Hu Wu (Desalination, 2026)

Synergistic modulation of nickel–manganese glycerate via sequential sulfurization and oxidation for high-performance battery–supercapacitor hybrids - Tsung-Rong Kuo; Lu-Yin Lin; Tzu-Han Chou; You-Zher Yu; Chutima Kongvarhodom; Sibidou Yougbaré; Muhammad Saukani; Hung-Ming Chen (Journal of Environmental Chemical Engineering, 2026)

A dual-function electroactive hydrogel platform for mitigating oxidative stress and restoring muscle function - Yi Lin; Zi-Hao Lin; Hai-Bin Jiang; Yu-Hao Kang; Qing-Song Deng; Rong-Tai Zuo; Zhi-Qi Lin; Er-Peng Yang; Jun-Jie Xu; Clara Chen; Xi-Ming Wang; Jin-Zhong Zhao (Chemical Engineering Journal, 2026)

Multidimensional evaluation and quantification of tunnel shotcrete roughness using point cloud data - Yun-Jian Cheng; Rong-Feng Chen; Ming-Xing Ye; Wen-Ge Qiu; Feng Lu (Tunnelling and Underground Space Technology, 2026)

Effect of dissolved organic matter chemical characters on microbial community of paddy soils in subtropical China - Yaxin Liu; Yingcong Ye; Daming Li; Rong Cui; Xiaoli Liu; Ling Chen; Meng Wu; Jia Liu; Xi Guo; Ming Liu (Soil and Tillage Research, 2026)

Engineering bimetallic Cobalt–Iron glycerate Co-Catalysts on bismuth vanadate for improved charge transfer and photoelectrochemical catalytic water oxidation - Tsung-Rong Kuo; He-Jin Li; Kai-Jie Chuang; Chutima Kongvarhodom; Sibidou Yougbaré; Muhammad Saukani; Hung-Ming Chen; Lu-Yin Lin (Fuel, 2026)

Callosobruchus maculatus feeding triggers multilevel defenses in cowpea seeds: from germination regulation to defensive metabolite biosynthesis - Hainuo Hong; Ming Zhang; Jiamei Geng; Qiulin Chen; Zheyi Shi; Yang Gao; Ying Zhou; Zeng‑Rong Zhu (Journal of Pest Science, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Phosphorus–boron synergistic carbonization/dormancy strategy enables polyurethane foams with aging enhanced fire safety - Shuang Li; Hai-Bo Zhao; Ming-Jun Chen; Lei He; Lin Zhang; Fu-Rong Zeng; Yu-Zhong Wang (Chemical Engineering Journal, 2026)

Os79, a UDP‐Glycosyltransferase, negatively regulates cadmium tolerance and accumulation in rice - Rui Guo; Hao Yu Wang; Chong Wei Zhong; Rong Rong Ma; Jiu Huang; Jin Chen; Xian Jiao Guan; Lu Zheng; Ren Fang Shen; Ming Qing Liu; Xiao Fang Zhu (Journal of Hazardous Materials, 2026)

A novel mitochondrial OMA1-DELE1-HRI axis mediates polystyrene microplastics-induced blood-testis barrier dysfunction - Rong Wang; Zhen Tian; Chen Chen; Ming-Ming Zhang; Ding-Qiang Peng; Ke-Xin Liu; Yu-Tong Ren; Shuai Lin; Qiang Hong; Yan-Li Ji; Yuan-Hua Chen (Journal of Environmental Sciences, 2026)

Debris flow vulnerability assessment in the Eastern Tibetan Plateau using integrated UAV-SLAM 3D reconstruction: Shuihaizigou Gully case study - Haoyu Li; Jianqiang Zhang; Yunyuan Li; Lili Zhang; Zaiyang Ming; Rong Chen (Landslides, 2026)

Genome-wide Identification and Expression Analysis of the ABF Gene Family in Achnatherum splendens - Shan Yin; Mingsu Chen; Ming Hu; XiaoYing Li; Jingru Wang; Jiahuan Niu; Zhangqi Song; Huan Yang; Hongbing Li; Rong Li (Plant Molecular Biology Reporter, 2026)

The TRAF6-TXNIP-NLRP3 signaling axis regulates LPS-induced pyroptosis in glomerular podocytes - Chunhua Ye; Hua Liu; Zhu Ming; Qinjun Yi; Rong Xiang; Yifu Chen (Journal of Molecular Histology, 2026)

Sorption and degradation of α-terpineol in soils with distinct physicochemical properties - Huan-Feng Chen; Zi-Jun Yang; Hai-Rong Chen; Hai-Ming Zhao; Yan-Wen Li; Quan-Ying Cai; Ce-Hui Mo; Lei Xiang (Environmental Geochemistry and Health, 2026)

Thioredoxin PgTRX acts as a protein elicitor to suppress green mold in citrus fruit via modulation of glutathione metabolism - Rong Zhu; Ou Chen; Yao Xu; Rui Huang; Wenjun Wang; Jian Ming; Kaifang Zeng (Postharvest Biology and Technology, 2026)

Corrigendum to “AI-driven process-tolerant BioFET sensing model for precise biliary atresia diagnosis of infants with a single drop of blood” [Chem. Eng. J. (2026), volume 531, 1 March 2026, 173939] - Chia-Kai Lin; Chi-Ming Ku; Chia-Che Wu; Yi-Fang Wu; Huey-Ling Chen; Yueh-Ju Hou; Arnab Pal; Zong-Hong Lin; Chee-Seng Lee; Tzong-Rong Ger; Yu-Lin Wang (Chemical Engineering Journal, 2026)

Chronic Excessive Exposure to Fluoride Impairs the Intestinal Mucosal Barrier to Cause Inflammatory Response and Microbiome Dysbiosis in Rats - Jia-Rong Zhang; Yi-Wen Li; Hong-Xuan Chen; Yi Luo; Ru-Ming Liu; Jian-Bin Wang; Ning-Ning Liu; Jian-Hui Xiao (Biological Trace Element Research, 2026)

RBOHC-derived ROS control plant nitrate starvation response via WRKYs-activated expression of high-affinity nitrate transporters - Tian Yuan; Meng-Qi Cui; Chen Xu; Jing-Ying Yan; Wo-Na Ding; Ji-Ming Xu; Yun-Rong Wu; Gui-Xin Li; Yu Liu; Dong Zhang; Chuan-Zao Mao; Moussa Benhamed; et al. (Science Bulletin, 2026)

AI-driven process-tolerant BioFET sensing model for precise biliary atresia diagnosis of infants with a single drop of blood - Chia-Kai Lin; Chi-Ming Ku; Chia-Che Wu; Yi-Fang Wu; Heuy-Ling Chen; Yueh-Ju Hou; Arnab Pal; Zong-Hong Lin; Chee-Seng Lee; Tzong-Rong Ger; Yu-Lin Wang (Chemical Engineering Journal, 2026)

Hydrogeophysical Imaging and Joint Interpretation of Rainfall Infiltration on an Embanked Slope in the Mid-Lower Yangtze Hilly Region - Rong-wen Guo; Chen-yang Li; Zhuo Liu; Deng-kang Wang; Ming Yu (Applied Geophysics, 2026)

Fine-tuning Atmospheric Parameters for Improving ENSO Simulation in the Zebiak–Cane Model - Xiaojun Wei; Lin Chen; Ming Sun; Ruihuang Xie; Rong-Hua Zhang (Advances in Atmospheric Sciences, 2026)

Biocontrol potential of the egg-larval parasitoid Chelonus bifoveolatus and egg parasitoid Telenomus remus against fall armyworm - Mi Huang; Zhen Shen; Yong-Ming Chen; Talha Tariq; Liang-De Tang; Qing-Rong Bai; Jian Wei; Kelvin Kamfwa; Nicolas Desneux; Lian-Sheng Zang (Crop Protection, 2026)

Electrohydrodynamic (EHD) drying of Polygonatum sibiricum: Kinetics, physicochemical quality, and energy efficiency analysis - Xin Li; Yunfeng Wang; Ming Li; Phavady Phoodthahaksa; Jiangtao Rong; Huai Chen; Qingyun Li; Xueping Tang; Min Xu; Tarek Kh Abdelkader (Journal of Stored Products Research, 2026)

Tuning Fe-P covalency via regenerative phosphorus vacancies for efficient aqueous cyclohexanone degradation - Han Feng; Zhengyi Lu; Ming Chen; Changming Zhong; Yongquan Wang; Rong Lin; Wenfeng Xu; Junming Hong (Environmental Research, 2026)

Interaction of secreted protein PgSLP and citrus calmodulin-like protein CsCML27/44 in fruit disease defense - Yao Xu; Ou Chen; Rong Zhu; Rui Huang; Jian Ming; Shixiang Yao; Kaifang Zeng (Postharvest Biology and Technology, 2025)

Labdane-type diterpenoids from Hypoestes phyllostachya inhibit pancreatic cancer stem cells - Tong Yan; Lin-Fen Ding; Ya Chen; Guo-Xian Hu; Lu Qu; Ming Hu; Ya-Xuan Ma; Rong-Qing Yuan; Lin Jia; Mei-Ju Zhao; Liu-Dong Song; Jia Su; et al. (Phytochemistry, 2025)

Microbial community assembly driven by dissolved organic matter and sulfate induces arsenic transformation in shallow aquifers of lateritic red soil regions - Ming-Zhu Chen; Jun-Feng Wang; Jian-Ping Ouyang; Yi-Rong Deng; Mei-Ting Yang; Yu-Dian Xun; Xiao-Hui Shi; Guang-Yong Tang; Jian-Ying Mo; Han-Jie Ye; Qu-Sheng Li (Journal of Hazardous Materials, 2025)

Tailoring nickel glycerate electrodes through precursor chemistry and sulfurization for enhanced battery-supercapacitor hybrid performance - Tsung-Rong Kuo; Yun-Hsi Wang; Bo-Yang Chuang; Chutima Kongvarhodom; Sibidou Yougbaré; Muhammad Saukani; Hung-Ming Chen; Lu-Yin Lin (Journal of Environmental Chemical Engineering, 2025)

An electrochemical reactor that enables continuous and uniform flow of high-viscosity slurry for semi-solid flow batteries - Chao Deng; Xiaoxin Li; Furong Xie; Miguel A. Modestino; Mustafa Kemal Bayazit; Barun Kumar Chakrabarti; Jeffrey Gostick; Zinan Wu; Rong Chen; Guo-Ming Weng (Chemical Engineering Journal, 2025)

Lithospermic acid targeting heat shock protein 90 attenuates LPS-induced inflammatory response via NF-кB signalling pathway in BV2 microglial cells - Jie Guo; Chen-guang Li; Feng-yi Mai; Jing-rong Liang; Ze-hao Chen; Jiao Luo; Ming-chao Zhou; Yu-long Wang; Wen-tao Yang (Immunologic Research, 2025)

Copper-Induced Nephropathy: Clinical Characterization of 36 Cases and Comprehensive Literature Review - Yi-Ling Li; Jing Chen; Jin-Rong Zhang; Ting-Ting Zhou; Jian-chao Peng; Zhi-Xin Huang; Kang Nong; Michael Aschner; Yue-Ming Jiang (Biological Trace Element Research, 2025)

New aromatic butenolides from the plant endophytic fungus Malbranchea umbrina D16 - Xian-An Chen; Han-Zhuang Weng; Lei-Ming Wu; Shu-Qi Wu; Rong Pu; Tao Yuan; Sheng Yin; Gui-Hua Tang (Natural Product Research, 2025)

Phylogeography of a Small Mammal ( Blarinella quadraticauda ) Distributed Around the Sichuan Basin, Southwest China - Qing Liu; Yu Deng; Rong‐Hui Fan; Chang‐Kun Fu; Xu‐Ming Wang; Shao‐Ying Liu; Shun‐De Chen (Zoologica Scripta, 2025)
The rapid climatic fluctuations and geographical factors during the Quaternary glacial period, particularly in the Pleistocene epoch, play a pivotal role in shaping intraspecific genetic diversity. We conducted an investigation into the genetic structure and speciation mechanisms of a small mammal species, Asiatic Short‐Tailed Shrew ( Blarinella quadraticauda ), which is mainly distributed in the mountains surrounding the Sichuan Basin and its adjacent regions in southwest China. Extensive sampling was conducted across the region (180 Asiatic Short‐Tailed Shrews from 67 sites), followed by principal component analysis and discriminant analysis on complete skull data. Phylogenetic analyses were conducted using mitochondrial (Cytb) and nuclear (APOB and BRCA1) genes. Additionally, the potentially suitable distribution range under both current and historical climatic conditions was projected. Our results show that B. quadraticauda in the Sichuan Basin is divided into six major clades, which are largely morphologically similar, except for the clade from Baoxing, Sichuan, which exhibits a slightly larger size. Additionally, the species exhibits a nearly ring‐like distribution around the Sichuan Basin. Genetic exchange among populations in the northern and eastern regions of the basin appears to be limited, suggesting potential barriers to gene flow. Under the influence of the basin's lowlands, the rapid climate oscillation of the Quaternary glacial period and the uplift of the Tibetan Plateau, the species appears to have formed a ring distribution in the Sichuan Basin. Moreover, we have also updated the taxonomy and distribution range of B. quadraticauda .

Interactions between soil and phyllosphere microbiomes modulate flavor formation of Qingxiang Tieguanyin Oolong Tea - Zhao Zhang; Xin-Rong Huang; Ming-Kang Jin; Le-Yang Yang; Jing-Jun Deng; Hu Li; Zhi-Ming Chen; Huo-Gui Su; Liang-De Xiao; Jin-Long Tang; Shun Li; Roy Neilson; et al. (Plant and Soil, 2025)

Enrofloxacin drives the ultra-selective enrichment of Ca. Kuenenia stuttgartiensis under microaerobic conditions - Jiaqi Zhang; Hao Zhang; Zhenyi Ma; Lin Zhou; Qi Zhang; Quan Zhang; Chuan Chen; Rong Li; Xiao-Ming Ji (Journal of Hazardous Materials, 2025)

Targeted and non-targeted analyses reveal trophic biomagnification of rubber-derived chemicals in an estuarine food web near China's largest rubber production region - Yuan Liu; Jia-Ming Zhou; Nian-Nian Wu; Shan Liu; Xiao-Liang Liao; Haijiang Wu; Lin Zhu; Heng-Xiang Li; Lang Lin; Rui Hou; Zhi-Hua Li; Xiang-Rong Xu; et al. (Journal of Hazardous Materials, 2025)

Different impacts of temperature and precipitation on vegetation net primary production of global marsh wetlands - Jiaqi Zhang; Meiling Zhao; Rong Ma; Mingming Feng; Chen Ding; Liyuan Wu; Xianguo Lu; Xiangjin Shen; Ming Jiang (Global and Planetary Change, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

An energy-saving pH-asymmetric electrolyzer for simultaneous methane conversion and hydrogen production - Rong Chen; Furong Xie; Zinan Wu; Xiaoxin Li; Chao Deng; Zhenpeng Yao; Guo-Ming Weng (Science Bulletin, 2025)

Complete genome sequence of Alteromonas sp. OM2203, a marine bacterium degrading Ulva prolifera polysaccharides - Ming-Chen Wang; Zhi-Qing Wang; Jia-Rong Liu; Na Wang; Zhen-Kun Li; Fei-Fei Li; Yu-Han Sang; Hui-Hui Fu (Marine Genomics, 2025)

Novel galactose-rich polysaccharide from Ganoderma lucidum: structural characterization and immunomodulatory activities - Zhou-Wei Wu; Xiao-Cui Liu; Chen-Xi Quan; Xin-Yu Tao; Yi-Luo; Xue-Fang Zhao; Xing-Rong Peng; Ming-Hua Qiu (Carbohydrate Polymers, 2025)

Seismic behavior of CFST components for shear walls using double corrugated steel plates - Xu Liao; Xian Li; Wei Li; Rong Su; Ming Chen (Engineering Structures, 2025)

Cessation of manure application diminishes the dissemination potential of antibiotic resistance genes by altering bacterial interaction patterns in soil–lettuce systems - Ruochen Li; Xin Pei; Ming Zhang; Xuhui Deng; Chengyuan Tao; Jiabao Wang; Xueli Chen; Nicholas Clarke; Lidia Sas-Paszt; Zongzhuan Shen; Rong Li; Qirong Shen (Applied Soil Ecology, 2025)

The recruitment of alkaline phosphatase-positive endogenous neural stem cells enables robust neurogenesis and neural pathways reconstruction following spinal cord injury - Rong-Jie Wu; Jia-Lin Liu; Zheng-Hong Chen; Jing Xu; Ying Ding; Hai-Yang Yu; Chuang-Ran Wu; Shang-Bin Yang; Rui Liu; Yi-Nan Guo; Yue Yang; Ting-Ting Wu; et al. (Chemical Engineering Journal, 2025)

Kinetics and morphology study of hydrate formation from CO2-H2O emulsion in glass beads - Ming-Long Wang; Yi-Fei Sun; Hong-Nan Chen; Jin-Rong Zhong; Dan Rao; Yu Liu; De-Jun Xuan; Bei Liu; Chang-Yu Sun; Guang-Jin Chen (Chemical Engineering Journal, 2025)

Manipulating molecular conformation of charge-transfer cocrystal for NIR-II absorption and light/thermal-responsive imaging - Yun Rong; Si-Qi Chen; Yu Dong Zhao; Sheng Zhuo; Yuan-Yuan Li; Jin-Zhuo Liu; Yi-Yi Ju; Yue-Min Xie; Liang-Sheng Liao; Ming-Peng Zhuo; Ke-Qin Zhang (Chemical Engineering Journal, 2025)

Addressing accuracy challenges in machine learning for debris flow susceptibility: Insights from the Yalong River basin - Zaiyang Ming; Jianqiang Zhang; Haiqing He; Lili Zhang; Rong Chen; Yang Jia (Journal of Mountain Science, 2025)

First report of Stagonosporopsis pogostemonis causing the fruit rot disease of Capsicum annuum L. in China - Mengting Zou; Banlop Leelahasilp; Ming-Rong Chen; Yu-Ru Wang; Yong Wang (Crop Protection, 2025)

Genomic analysis of Vibrio sp. D3 reveals its role in marine sulfur cycling - Fei-Fei Li; Zhen-Kun Li; Ming-Chen Wang; Jia-Rong Liu; Na Wang; Zhi-Qing Wang; Yu-Zhong Zhang; Hui-Hui Fu (Marine Genomics, 2025)

Simultaneous recovery of water and antiscalant from cooling tower blowdown water by electrodialysis: Mechanism and cost-effectiveness - Jia-Rong Li; Jing-Han Wei; Yu-Chen Jin; Xian-Qiu Zhang; Hai-Ou Song; Ming-Xia Du (Journal of Cleaner Production, 2025)

Synergetic “amine scissors” break down cured epoxy resins with nearly 100% degradation efficiency - Furong Xie; Rong Chen; Chao Deng; Xiaoxin Li; Huiyan Yang; Yu Xie; Song Wang; Guo-Ming Weng (Chemical Engineering Journal, 2025)

Legume intercropping improves soil organic carbon stability in drylands: A 7-year experimental validation - Wei Wang; Meng-Ying Li; Yang Wang; Jian-Ming Li; Wei Zhang; Qin-Hui Wen; Shuang-Jin Huang; Guang-Rong Chen; Shuang-Guo Zhu; Jing Wang; Fazal Ullah; You-Cai Xiong (Agriculture, Ecosystems & Environment, 2025)

Identification of Potential Causal Genes for Neurodegenerative Diseases by Mitochondria-Related Genome-Wide Mendelian Randomization - Kang-Fu Yin; Ting Chen; Xiao-Jing Gu; Zheng Jiang; Wei-Ming Su; Qing-Qing Duan; Xiang-Jin Wen; Bei Cao; Ju-Rong Li; Li-Yi Chi; Yong-Ping Chen (Molecular Neurobiology, 2025)

Comammox and ammonia-oxidizing archaea dominated the nitrification under different nitrogen fertilizer levels in acid purple soil of Southwest China - Jun Xie; Jianguo Jiang; Jie Lu; Wencai Dai; Huarong Guo; Yuanxue Chen; Rong Huang; Zifang Wang; Ming Gao (Applied Soil Ecology, 2025)

Microplastic pollution in stony coral skeletons and tissues: A case study of accumulation and interrelationship in South Penghu Marine National Park, Taiwan Strait - Chih-Feng Chen; Yun-Ru Ju; Ming-Huang Wang; Yee Cheng Lim; Chiu-Wen Chen; Yu-Rong Cheng; Cheng-Di Dong (Journal of Hazardous Materials, 2025)

Structurally diversified sesquiterpenoids from Chloranthus henryi and their neuroprotective activities on H2O2 damaged PC12 cells - Meng-Li He; Lian-Lian Xu; Yang Liu; Yan-Ping Gao; Yong-Ming Luo; Rong-Cai Yue; Fang-You Chen (Phytochemistry, 2025)

Long-term nitrogen application decreased mineral-associated organic carbon while increasing particulate organic carbon in purple soil in southwest China - Jun Xie; Yuanxue Chen; Rong Huang; Wencai Dai; Jie Lu; Zifang Wang; Ming Gao (Journal of Environmental Management, 2025)

Effect of Maillard reaction on the allergenicity of crude extract of Mactra quadrangularis - Fa-Jie Li; Xin-Rong He; Dong-Xiao Li; Yang Yang; Shuai Kang; Qing-Mei Liu; Lian-Zhong Luo; Gui-Xia Chen; Guang-Ming Liu (Food Research International, 2025)

A new approach to high conversion CO2 hydrate sequestration by CO2/water emulsion injection into marine sediments - Ming-Long Wang; Yi-Fei Sun; Hong-Nan Chen; Jin-Rong Zhong; Liang-Liang Ren; Ming Wang; Dan Rao; Yong-Quan Liu; Yi-Bo Hao; Bei Liu; Chang-Yu Sun; Guang-Jin Chen (Chemical Engineering Journal, 2025)

Neutral purple soil acidification and mineralogical property changes due to long-term urea application in southwest China - Jun Xie; Dan Wang; Yuanxue Chen; Zhiqi Li; Wencai Dai; Rong Huang; Zifang Wang; Ming Gao (Soil and Tillage Research, 2024)

Associations between volatile organic compounds exposure and multiple oxidative damage biomarkers: Method development, human exposure, and application for e-waste pollution prediction - Jia-Rong Wang; Hong-Xuan Kuang; Ye Liu; Xin-Yi Li; Tian-Hong Chen; Xiao-Hui Zhu; Rui-Fang Fan; Ming-Deng Xiang; Yun-Jiang Yu (Science of The Total Environment, 2024)

Effects of changing spatial scale on debris-flow hazard assessment: A case study in the Dadu River basin, China - Lili Zhang; Jianqiang Zhang; Zaiyang Ming; Haoyu Li; Rong Chen; Yang Jia (Science of The Total Environment, 2024)

The different impacts of functional network centrality and connectivity on the complexity of brain signals in healthy control and first-episode drug-naïve patients with major depressive disorder - Shanling Ji; Wei An; Jing Zhang; Cong Zhou; Chao-Gan Yan; Xiao Chen; Li-Ping Cao; Wei Chen; Yu-Qi Cheng; Yi-Ru Fang; Qi-Yong Gong; Wen-Bin Guo; et al. (Brain Imaging and Behavior, 2024)

Quantitative evaluation of hydrate-based CO2 storage in unsealed marine sediments: Viewpoint from the driving force of hydrate formation and CO2-water contact ability - Hong-Nan Chen; Yi-Fei Sun; Wei-Xin Pang; Ming-Long Wang; Ming Wang; Jin-Rong Zhong; Liang-Liang Ren; Bo-Jian Cao; Dan Rao; Chang-Yu Sun; Guang-Jin Chen (Fuel, 2024)

Enhanced hydrate formation at the liquid CO2-brine interface with shear flow for solid CO2 sequestration - Ming-Long Wang; Yi-Fei Sun; Wei-Xin Pang; Qing-Ping Li; Ting Huang; Hong-Nan Chen; Ming Wang; Jin-Rong Zhong; Liang-Liang Ren; Dan Rao; Bei Liu; Chang-Yu Sun; et al. (Gas Science and Engineering, 2024)

Decapod iridescent virus 1 (DIV1) 168L can target cuticle protein 8 from Litopenaeus vannamei - Qin Zheng; Huan-huan Rao; Fu-Rong Zhao; Xiao-Juan Chen; Wei Wang; Jian-Ming Chen (Journal of Invertebrate Pathology, 2024)

Structured carbon for electromagnetic shielding and microwave absorption from carbonization of waste Polymer: A review - Jiang-Tao Liu; Yu-Chen Zheng; Xin Hou; Xue-Rong Feng; Ke Jiang; Ming Wang (Chemical Engineering Journal, 2024)

Bibliometric study of the application of the chicken embryo chorioallantoic membrane model in cancer research: the top 100 most cited articles - Chang Song; Dan-Dan Xiong; Rong-Quan He; Xiang-Zhi Yong; Zhi-Guang Huang; Yi-Wu Dang; Gang Chen; Yu-Yan Pang; Chun-Yan Zhao; Ning Qu; Dan-Ming Wei (Journal of Comparative Pathology, 2024)

Elevational distribution of forests and its spatiotemporal dynamics in subtropical China from 2000 to 2019 - Zhencan Zheng; Liuwen Zhuang; Guofang Miao; Han Liu; Zhiqiang Cheng; Wenyu Li; Rong Shang; Peng Gong; Jing Ming Chen (Science China Earth Sciences, 2024)

Identification of the Galactinol Synthase (GolS) Family in Medicago truncatula and Expression Analysis Under Abiotic Stress and Phytohormone Treatment - Hua Li; Ying Di Gao; Li Qing Kang; Hong Yang Yu; Li Ming Zeng; Yi Hua Wang; Rong Rong Chen; Jian Bo Song (Journal of Plant Growth Regulation, 2024)

Real-time ozonation monitoring and control in wastewater tertiary treatment: An ultraviolet-visible monitoring approach - Yunze Rong; Xiaodong Wang; Ming Zhu; Wei Chen; Zakhar Maletskyi; Harsha Ratnaweera; Xuejun Bi (Journal of Water Process Engineering, 2024)

Capnesterones A and B, new steroids isolated from the soft coral Capnella imbricata - Ting-Yu Cheng; Chia-Jung Yang; Po-Jen Chen; Yu-Li Chen; Bo-Rong Peng; Te-An Kung; Zhi-Hong Wen; Kuei-Hung Lai; Hsu-Ming Chung (Phytochemistry Letters, 2024)

Environmentally relevant concentrations of benzophenones exposure disrupt intestinal homeostasis, impair the intestinal barrier, and induce inflammation in mice - Yu-Jia Lin; Hong-Mei Li; Yan-Rong Gao; Ping-Fan Wu; Bin Cheng; Chen-Long Yu; Yu-Xin Sheng; Hai-Ming Xu (Environmental Pollution, 2024)

Chemical constituents of the deep-sea-derived fungus Trichoderma simmonsii ZEN3 and their chemotaxonomic significance - Li-Fang Liu; Yuan Wang; Rong Chao; Lin Xu; Zheng-Biao Zou; Kai Zhang; Ming-Min Xie; Xian-Qiang Chen; Cheng-Hai Gao; Xian-Wen Yang (Biochemical Systematics and Ecology, 2024)

Climate change-induced impacts on PM2.5 in Taiwan under 2 and 4 °C global warming - I-Chun Tsai; Pei-Rong Hsieh; Huang-Hsiung Hsu; Yu-Shiang Tung; Yung-Ming Chen; Chao-Tzuen Cheng (Atmospheric Pollution Research, 2024)

The potential use of Zymomonas mobilis for the food industry - Lu Liu; Jian-Ting Li; Sheng-Hao Li; Lin-Pei Liu; Bo Wu; Yan-Wei Wang; Shi-hui Yang; Cheng-Han Chen; Fu-Rong Tan; Ming-Xiong He (Critical Reviews in Food Science and Nutrition, 2024)

Contact-electro-catalysis for degradation of trace antibiotics in wastewater - Da-Qi Cao; Rong-Kun Fang; Yi-Xuan Song; Ming-Guo Ma; Haiyan Li; Xiao-Di Hao; Rongling Wu; Xiangyu Chen (Chemical Engineering Journal, 2024)

Efficient magnetic solid-phase extraction, UPLC-MS/MS detection, and consumption assessment of five trace psychoactive substances - Rong Zhu; Shurui Cao; Hongtao Su; Dewang Ming; Yao Tang; Zhiqiong Chen (Environmental Science and Pollution Research, 2024)

Myosin heavy chain isoform expression and meat quality characteristics of different muscles in yak (Bos grunniens) - Xueyuan Bai; Feng Yin; Ang Ru; Ming Li; Wei Tian; Guiyan Zhang; Qingwen Chen; Rong Chai; Yanxia Liu; Wenming Cui; Hongmei Shi; Chaozhi Zhu; et al. (Meat Science, 2024)

High-throughput analytical methodology of monoalkyl phthalate esters and the composite risk assessment with their parent phthalate esters in aquatic organisms and seawater - Qiang-Qiang Shi; Feng Xu; Tao Shen; Rong-Rong Zhang; Hua Liu; Ming-Ze Chen; Ai-Li Sun; Ze-Ming Zhang; Xi-Zhi Shi (Journal of Hazardous Materials, 2024)

Anemoside B4, a new pyruvate carboxylase inhibitor, alleviates colitis by reprogramming macrophage function - Qing-hua Liang; Qiu-rong Li; Zhong Chen; Li-juan Lv; Yu Lin; Hong-lv Jiang; Ke-xin Wang; Ming-yue Xiao; Nai-xin Kang; Peng-fei Tu; Shi-liang Ji; Ke-jun Deng; et al. (Inflammation Research, 2024)

Exploration of the Catalytic Cycle Dynamics of Vigna Radiata H+–Translocating Pyrophosphatases Through Hydrogen–Deuterium Exchange Mass Spectrometry - Li-Kun Huang; Yi-Cyuan Huang; Pin-Chuan Chen; Ching-Hung Lee; Shih-Ming Lin; Yuan-Hao Howard Hsu; Rong-Long Pan (The Journal of Membrane Biology, 2023)

Acquisition parameters and sensitivity analysis affecting the seismic imaging quality of the complex piedmont zone - Hu Zhao; Wen-jun Li; Yong Wu; Zhi-xin Di; Rong-rong Zhao; Wei Chen; Ming-yi Li (Applied Geophysics, 2023)

Curcumin-mediated photodynamic treatment extends the shelf life of salmon (Salmo salar) sashimi during chilled storage: Comparisons of preservation effects with five natural preservatives - Hui-Ming Chen; Quan Zhou; Li-Jun Huang; Jun Lin; Jia-Fei Liu; Zi-Yong Huang; Rong-Lin Zhang; Jing-Jing Wang; Yong Zhao; Yong-Ning Wu; Xing-Fen Yang; Wei-Liang Wu (Food Research International, 2023)

Recent advances in nanofiltration-based hybrid processes - Tian-Zhi Jia; Ming-Yue Rong; Chang-Tao Chen; Wai Fen Yong; Siew Kei Lau; Rong-Fei Zhou; Min Chen; Shi-Peng Sun (Desalination, 2023)

Synergistic driving effects of risk factors on human brucellosis in Datong City, China: A dynamic perspective from spatial heterogeneity - Li Shen; Ming-hao Sun; Wen-tao Ma; Qing-wu Hu; Chen-xi Zhao; Zu-rong Yang; Cheng-hao Jiang; Zhong-jun Shao; Kun Liu (Science of The Total Environment, 2023)

Structure-diversified terpenoids from Salvia prattii and their protective activity against alcoholic liver diseases - Xiu-wen Yin; Xiang-xiang Bian; Yan-fang Chen; Ming Zhang; Lan Wu; Fu-cai Ren; Fu-rong Yang; Xiang-dong Pu; Bing-yuan Yang; Chuan-pu Shen (Phytochemistry, 2023)

Icariin inhibits hypertrophy by regulation of GPER1 and CaMKII/HDAC4/MEF2C signaling crosstalk in ovariectomized mice - Wenxia Zhao; Xiaoli Shan; Xueqin Li; Shuang Lu; Lei Xia; Huihua Chen; Chen Zhang; Wei Guo; Ming Xu; Rong Lu; Pei Zhao (Chemico-Biological Interactions, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Characteristics of mesenchymal stem cells and their exosomes derived from giant panda (Ailuropoda melanoleuca) endometrium - Yu-Liang Liu; Jia-Song Chen; Jun-Hui An; Zhi-Gang Cai; Jing-Chao Lan; Yuan Li; Xiang-Wei Kong; Ming-Yue Zhang; Rong Hou; Dong-Hui Wang (In Vitro Cellular & Developmental Biology - Animal, 2023)

Constructing electron transport channels in FeSe2 microspheres by a facile strategy for superior long-life and ultrafast sodium-ion storage - Ming Xu; Yu Ma; Rong Liu; Huanhao Xiao; Liming Chen; Ziqiang Zhang; Lei Wang; Guohui Yuan (Chemical Engineering Journal, 2023)

Microbial diversity and functional profiling in coastal tidal flat sediment with pollution of nutrients and potentially toxic elements - Yihong Yue; Huanan Rong; Zhihong Yang; Xueyang Pan; Yin Chen; Ming Yang (Journal of Soils and Sediments, 2023)

HSPA12A was identified as a key driver in colorectal cancer GWAS loci 10q26.12 and modulated by an enhancer–promoter interaction - Zequn Lu; Linyun Fan; Fuwei Zhang; Chaoqun Huang; Yimin Cai; Can Chen; Gaoyuan Li; Ming Zhang; Jinyu Huang; Caibo Ning; Yanmin Li; Wenzhuo Wang; et al. (Archives of Toxicology, 2023)

The city-wide full-scale interactive application of sewage surveillance programme for assisting real-time COVID-19 pandemic control – A case study in Hong Kong - Wai-yin Ng; Wai Thoe; Rong Yang; Wai-ping Cheung; Che-kong Chen; King-ho To; Kan-ming Pak; Hon-wan Leung; Wai-kwan Lai; Tsz-kin Wong; Tat-kwong Lau; Ka-wing Au; et al. (Science of The Total Environment, 2023)

Anti-inflammatory cembrane-based diterpenoids isolated from the octocoral Sinularia querciformis - Te-An Kung; Lo-Yun Chen; Chia-Ying Li; Bo-Rong Peng; Tsong-Long Hwang; Ping-Jyun Sung; Kuei-Hung Lai; Hsu-Ming Chung (Phytochemistry Letters, 2023)

Responses of Bacillus sp. under Cu(II) stress in relation to extracellular polymeric substances and functional gene expression level - Ling-ling Wang; Zheng-yan Yin; Yun Xu; Miao-yu Deng; Kai-ming Zhang; Quan Wang; Rong-ping Chen; Lei Yu (Environmental Science and Pollution Research, 2023)

Quantum neuronal sensing of quantum many-body states on a 61-qubit programmable superconducting processor - Ming Gong; He-Liang Huang; Shiyu Wang; Chu Guo; Shaowei Li; Yulin Wu; Qingling Zhu; Youwei Zhao; Shaojun Guo; Haoran Qian; Yangsen Ye; Chen Zha; et al. (Science Bulletin, 2023)

Overexpression of Sedum SpHMA2, SpHMA3 and SpNramp6 in Brassica napus increases multiple heavy metals accumulation for phytoextraction - Zi Yang; Hai-Tao Wu; Hao Yang; Wan-Di Chen; Jia-Lan Liu; Fan Yang; Li Tai; Bin-Bin Li; Bo Yuan; Wen-Ting Liu; Yan-Feng Zhang; Yan-Rong Luo; et al. (Journal of Hazardous Materials, 2023)

QTL-seq and transcriptomic integrative analyses reveal two positively regulated genes that control the low-temperature germination ability of MTP–maize introgression lines - Ru-Yu He; Jun-Jun Zheng; Yu Chen; Ze-Yang Pan; Tao Yang; Yang Zhou; Xiao-Feng Li; Xinyi Nan; Ying-Zheng Li; Ming-Jun Cheng; Yan Li; Yang Li; et al. (Theoretical and Applied Genetics, 2023)

Orange protein (DbOR) from the salt-tolerant green alga Dunaliella bardawil mediates photosynthesis against heat stress via interacting with DbPsbP1 - Ming-Hua Liang; Jv-Liang Dai; Shan-Rong Xie; Jing-Xuan Wu; Hao-Hong Chen; Jian-Guo Jiang (Algal Research, 2023)

Transcriptome sequencing and metabolite analysis reveal the single and combined effects of microplastics and di-(2-ethylhexyl) phthalate on Peneaus vannamei - Qiang-Qiang Shi; Xiao-Qian Zhang; Ze-Ming Zhang; Ning-Bo Wang; Hua Liu; Rong-Rong Zhang; Ai-Li Sun; Jiong Chen; Xi-Zhi Shi (Science of The Total Environment, 2023)

Cumulative effects of temperature on blood pressure during pregnancy: A cohort study of differing effects in three trimesters - Qi Chen; Ya Wang; Hui-Rong Tang; Yuan Wang; Ai-Hua Gu; Xiang-Jun Zhai; Ming-Ming Zheng (Science of The Total Environment, 2023)

Mineral residue accelerant-enhanced anaerobic digestion of cow manure: An evaluation system of comprehensive performance - Sining Yun; Tian Xing; Yi Wang; Rong Chen; Feng Han; Chen Zhang; Ming Zou (Science of The Total Environment, 2023)

Elevated Levels of Naturally-Occurring Autoantibodies Against the Extracellular Domain of p75NTR Aggravate the Pathology of Alzheimer’s Disease - Chen-Yang He; Ding-Yuan Tian; Si-Han Chen; Wang-Sheng Jin; Yuan Cheng; Jia-Yan Xin; Wei-Wei Li; Gui-Hua Zeng; Cheng-Rong Tan; Jie-Ming Jian; Dong-Yu Fan; Jun-Rong Ren; et al. (Neuroscience Bulletin, 2023)

Simultaneous determination of benzothiazoles, benzotriazoles, and benzotriazole UV absorbers by solid-phase extraction-gas chromatography-mass spectrometry - Ming-Liang Zhao; Yan Chen; Gui-Peng Yang; Rong Chen (Environmental Science and Pollution Research, 2023)

A hyperspectral image reconstruction algorithm based on RGB image using multi-scale atrous residual convolution network - Shaoxiang Hu; Rong Hou; Luo Ming; Su Meifang; Peng Chen (Frontiers in Marine Science, 2023)
Hyperspectral images are a valuable tool for remotely sensing important characteristics of a variety of landscapes, including water quality and the status of marine disasters. However, hyperspectral data are rare or expensive to obtain, which has spurred interest in low-cost, fast methods for reconstructing hyperspectral data from much more common RGB images. We designed a novel algorithm to achieve this goal using multi-scale atrous convolution residual network (MACRN). The algorithm includes three parts: low-level feature extraction, high-level feature extraction, and feature transformation. The high-level feature extraction module is composed of cascading multi-scale atrous convolution residual blocks (ACRB). It stacks multiple modules to form a depth network for extracting high-level features from the RGB image used as an input. The algorithm uses jump connection for residual learning, and the final high-level feature combines the output of the low-level feature extraction module and the output of the cascaded atrous convolution residual block element by element, so as to prevent gradient dispersion and gradient explosion in the deep network. Without adding too many parameters, the model can extract multi-scale features under different receptive fields, make better use of the spatial information in RGB images, and enrich the contextual information. As a proof of concept, we ran an experiment using the algorithm to reconstruct hyperspectral Sentinel-2 satellite data from the northern coast of Australia. The algorithm achieves hyperspectral spectral reconstruction in 443nm-2190nm band with less computational cost, and the results are stable. On the Realworld dataset, the reconstruction error MARE index is less than 0.0645, and the reconstruction time is less than 9.24S. Therefore, in the near infrared band, MACRN reconstruction accuracy is significantly better than other spectral reconstruction algorithms. MACRN hyperspectral reconstruction algorithm has the characteristics of low reconstruction cost and high reconstruction accuracy, and its advantages in ocean spectral reconstruction are more obvious.

An approach to the high efficient exploitation of nature gas hydrate and carbon sequestration via injecting CO2/H2 gas mixture with varying composition - Bo-Jian Cao; Yi-Fei Sun; Hong-Nan Chen; Jin-Rong Zhong; Ming-Long Wang; Meng-Ya Niu; Jing-Yu Kan; Chang-Yu Sun; Dao-Yi Chen; Guang-Jin Chen (Chemical Engineering Journal, 2023)

Acinetobacter faecalis Sp. Nov., Isolated from Elephant Faeces - Xue-Mei Chen; De-Feng An; Si-Rong He; Shao-Juan Yang; Zu-Zhen Yang; Lian-Shuang Xiong; Gui-Ding Li; Ming-Guo Jiang; Cheng-Lin Jiang; Yi Jiang (Current Microbiology, 2023)

Indigodole E from Strobilanthes cusia exhibits anti-IL-17A effect - Chia-Lin Lee; Chien-Ming Wang; Hung-Rong Yen; Ying-Chyi Song; Chao-Jung Chen (Natural Product Research, 2022)

Changes in amino acid and fatty acid composition during early development in cobia (Rachycentron canadum) - Jian-sheng Huang; Rong-xin Li; Rui-tao Xie; You-ming Chen; Jian-dong Zhang; Eric Amenyogbe; Gang Chen (Frontiers in Marine Science, 2022)
An estimation of the utilization of endogenous nutrients from the yolk sac that occurs during embryonic and early larval development can be a valuable approach to studying the nutritional requirements of fish larvae. In this study, fertilized eggs, embryos (before the membrane, 24 hours after fertilization), newly-hatched larvae (0-d-old), and open-mouthed larvae (3-day-old, unfed rotifers) samples of cobia ( Rachycentron canadum ) were collected to determine the amino acid and fatty acid profiles. Crude protein composition varies significantly for cobia during the different stages of development. The total amino acids, except for lysine(Lys), histidine (His), methionine(Met), serine(Ser), and glycine(Gly), had no significant change in the early development stage ( P > 0.05); the content of other six essential amino acids (EAA) and six non-essential amino acids (NEAA) was consistent with the changing trend of total essential amino acid. From hatching newly hatched larvae to open-mouthed larvae, except for Leu, Phe and Ser, decreased significantly ( P <0.05). From the utilization rate of FAA, the utilization rate of Lys and Leu was the highest (60.26%) and (52.21%) in the embryonic and endogenous nutritional stages, respectively. The water content of the open-mouthed larvae of cobia was significantly higher than that of the fertilized eggs, embryos, and newly hatched larvae ( P < 0.05). Three kinds of saturated fatty acids (SFA), five kinds of monounsaturated fatty acids (MUFA), and eight kinds of polyunsaturated fatty acids (PUFA) were detected in the dry samples of each developmental stage. Based on these results, juvenile cobia can thrive with a wide range of crude protein concentrations. Further refinement of commercial cobia production feeds would have beneficial consequences for economic and environmental concerns due to the positive impacts of optimizing the protein component as well as the ability to maintain the rapid growth rates. The results show that the larval development of cobia needs to consume large amounts of n3PUFA (especially DHA and EPA) to improve the larvae’s survival rate. Research methods will always have limitations when evaluating the relationship between early life nutrition interventions and well-being outcomes later in life. This study provides essential information regarding cobia larvae’s fatty acid requirements.

Naturally-Occurring Antibodies Against Bim are Decreased in Alzheimer’s Disease and Attenuate AD-type Pathology in a Mouse Model - Jie-Ming Jian; Dong-Yu Fan; Ding-Yuan Tian; Yuan Cheng; Pu-Yang Sun; Cheng-Rong Tan; Gui-Hua Zeng; Chen-Yang He; Ye-Ran Wang; Jie Zhu; Xiu-Qing Yao; Yan-Jiang Wang; et al. (Neuroscience Bulletin, 2022)

Identification of the Largest SCA36 Pedigree in Asia: with Multimodel Neuroimaging Evaluation for the First Time - Yue Xie; Zhao Chen; Zhe Long; Rui-Ting Chen; Yi-Zheng Jiang; Ming-Jie Liu; Lin-Liu Peng; Hui-Rong Peng; Na Wan; Guangdong Zou; Chun-Rong Wang; Yu-Ting Shi; et al. (The Cerebellum, 2022)

Monascuslactams A–D, cytotoxic γ-lactams from marine fungus Monascus albidus BB3 - Qi Guo; Xiao-Ming Dai; Wen-Jian Lan; Liu-Ping Chen; Chi-Keung Lam; Gong-Kan Feng; Rong Deng; Xiao-Feng Zhu; Hou-Jin Li (Natural Product Research, 2022)

Identification and management of GCK-MODY complicating pregnancy in Chinese patients with gestational diabetes - Yanyan Jiang; Fusong Jiang; Ming Li; Qingkai Wu; Chenming Xu; Rong Zhang; Mingqiang Song; Yanzhong Wang; Ying Wang; Yating Chen; Juan Zhang; Xiaoxu Ge; et al. (Molecular and Cellular Biochemistry, 2022)

Flavonoid glycosides from the nectar of Camellia reticulata Lindl. - Xin-Lan Chen; Xing-Rong Peng; Xue-Yang Gong; Yi-Qiu Liu; Zhuo Qing; Xiao-Xiao Ren; Rui Su; Li-Ming Fang; Ming-Hua Qiu; Kun Dong (Natural Product Research, 2022)

Yak Excreta Application Alter Nitrification by Regulating the Ammonia-Oxidizing Bacterial Communities in Wetland Soils - Li Chen; Rong Bo Zheng; Jun Qin Gao; Ming Hua Song; Xue Lian Guo (Journal of Soil Science and Plant Nutrition, 2021)

Activation of the Hippocampal LXRβ Improves Sleep-Deprived Cognitive Impairment by Inhibiting Neuroinflammation - Chen Qiu; Min Wang; Wen Yu; Zheng Rong; He-Sheng Zheng; Ting Sun; Shui-Bing Liu; Ming-Gao Zhao; Yu-Mei Wu (Molecular Neurobiology, 2021)

Quantitative Proteomics Analysis of Sugarcane Ratoon Crop Chlorosis - Ye-Geng Fan; Rong-Fa Chen; Li-Hang Qiu; Zhong-Feng Zhou; Hui-Wen Zhou; Ji-Guang Wei; Xiu-Peng Song; Ting Luo; Prakash Lakshmanan; Xing Huang; Jian-Ming Wu; Yang-Rui Li (Sugar Tech, 2021)

Simultaneous detection of multiple bacterial and viral aquatic pathogens using a fluorogenic loop‐mediated isothermal amplification‐based dual‐sample microfluidic chip - Qian‐Jin Zhou; Jian‐Fei Lu; Xiu‐Rong Su; Jing‐Lei Jin; Shang‐Yang Li; Yan Zhou; Lei Wang; Xin‐Bin Shao; Yao‐Hua Wang; Mao‐Cang Yan; Ming‐Yun Li; Jiong Chen (Journal of Fish Diseases, 2021)
Rapid and user‐friendly diagnostic tests are necessary for early diagnosis and immediate detection of diseases, particularly for on‐site screening of pathogenic microorganisms in aquaculture. In this study, we developed a dual‐sample microfluidic chip integrated with a real‐time fluorogenic loop‐mediated isothermal amplification assay (dual‐sample on‐chip LAMP) to simultaneously detect 10 pathogenic microorganisms, that is Aeromonas hydrophila , Edwardsiella tarda , Vibrio harveyi , V. alginolyticus , V. anguillarum , V. parahaemolyticus , V. vulnificus , infectious hypodermal and haematopoietic necrosis virus, infectious spleen and kidney necrosis virus, and white spot syndrome virus. This on‐chip LAMP provided a nearly automated protocol that can analyse two samples simultaneously, and the tests achieved limits of detection (LOD) ranging from 10 0 to 10 –1 pg/μl for genomic DNA of tested bacteria and 10 –4 to 10 –5 pg/μl for recombinant plasmid DNA of tested viruses, with run times averaging less than 30 min. The coefficient of variation for the time‐to‐positive value was less than 10%, reflecting a robust reproducibility. The clinical sensitivity and specificity were 93.52% and 85.53%, respectively, compared to conventional microbiological or clinical methods. The on‐chip LAMP assay provides an effective dual‐sample and multiple pathogen analysis, and thus would be applicable to on‐site detection and routine monitoring of multiple pathogens in aquaculture.

Geochemical characteristics and geological significance of chert nodules in Qixia formation, Pingding Mountain, lower Yangtze Plate - Jun Li; Lu-wang Chen; Chun-ming Hao; Jie Zhang; Song Chen; He-rong Gui (Journal of Mountain Science, 2021)

Cathepsin V Mediates the Tazarotene-induced Gene 1-induced Reduction in Invasion in Colorectal Cancer Cells - Chun-Hua Wang; Lu-Kai Wang; Chang-Chieh Wu; Mao-Liang Chen; Chan-Yen Kuo; Rong-Yaun Shyu; Fu-Ming Tsai (Cell Biochemistry and Biophysics, 2020)

Identification of Ala2Thr mutation in insulin gene from a Chinese MODY10 family - Juan Zhang; Yanjun Liu; Ming Li; Xiaoxu Ge; Ying Wang; Xin Huang; Di Yang; Rong Zhang; Yating Chen; Ming Lu; Jun Yin; Mingqiang Song; et al. (Molecular and Cellular Biochemistry, 2020)

Capture of Ralstonia solanacearum species complex strains directly from plant tissue sampled on FTA cards for molecular characterization - Rishi R. Burlakoti; Chiou-fen Hsu; Jaw-rong Chen; Zong-Ming Sheu; Wubetu Bihon; Lawrence Kenyon (Journal of Plant Pathology, 2020)

Preparation and In vitro Evaluation of FDM 3D-Printed Ellipsoid-Shaped Gastric Floating Tablets with Low Infill Percentages - Di Chen; Xiang-Yu Xu; Rui Li; Gen-Ao Zang; Yue Zhang; Ming-Rui Wang; Meng-Fei Xiong; Jia-Rui Xu; Ting Wang; Hui Fu; Qin Hu; Bin Wu; et al. (AAPS PharmSciTech, 2020)

Effects of Exogenous GA3 and DPC Treatments on Levels of Endogenous Hormone and Expression of Key Gibberellin Biosynthesis Pathway Genes During Stem Elongation in Sugarcane - Li-Hang Qiu; Rong-Fa Chen; Han-Min Luo; Ye-Geng Fan; Xing Huang; Jun-Xian Liu; Fa-Qian Xiong; Hui-Wen Zhou; Chong-Kun Gan; Jian-Ming Wu; Yang-Rui Li (Sugar Tech, 2019)

De novo assembly and transcriptome analysis of differentially expressed genes relevant to variegation in hawthorn flowers - Wei Ji; Wei Zhao; Rong-Chen Liu; Xiao-Bo Jiao; Kai Han; Zhong-Yi Yang; Mei-Ying Gao; Rui Ren; Xiu-Juan Fan; Ming-Xia Yang (Plant Biotechnology Reports, 2019)

Do arbuscular mycorrhizal fungi help the native species Bidens biternata resist the invasion of Bidens alba? - Jun-Kang Cheng; Mao-Feng Yue; Heng-Rong Yang; Bao-Ming Chen; Guo-Rong Xin (Plant and Soil, 2019)

Skin test of tuberculin purified protein derivatives with a dissolving microneedle-array patch - Wei Wang; Hou Ming Liu; Jing Zhou; Yu Guang Wang; Xi Feng; Hao Tang; Qinying Yan; Rong Sheng Zhu; Yu Wei Wu; Xing Guo Wang; Dan He; Fan Chen (Drug Delivery and Translational Research, 2019)

Cloud Radiative Feedbacks during the ENSO Cycle Simulated by CAMS-CSM - Lin Chen; Lijuan Hua; Xinyao Rong; Jian Li; Lu Wang; Guo Zhang; Ming Sun; Zi’an Ge (Journal of Meteorological Research, 2019)

New pyrazinoquinazoline alkaloids Isolated from a culture of Stenotrophomonas maltophilia QB-77 - Sheng-Yan Qian; Cai-Ling Yang; Afsar Khan; Rong-Xiang Chen; Ming-Song Wu; Li Tuo; Qian Wang; Jian-Guo Liu; Gui-Guang Cheng (Natural Product Research, 2019)

Two new benzophenones and one new natural amide alkaloid isolated from a mangrove-derived Fungus Penicillium citrinum - Cai-Juan Zheng; Hai-Xia Liao; Rong-Qing Mei; Guo-Lei Huang; Lu-Jia Yang; Xue-Ming Zhou; Tai-Ming Shao; Guang-Ying Chen; Chang-Yun Wang (Natural Product Research, 2019)

Insights into the effect of chemical treatment on the physicochemical characteristics and adsorption behavior of pig manure-derived biochars - Rong-Zhong Wang; Dan-Lian Huang; Chen Zhang; Yun-Guo Liu; Guang-Ming Zeng; Cui Lai; Xiao-Min Gong; Min Cheng; Jia Wan; Qing Zhang (Environmental Science and Pollution Research, 2019)

Lamelloplasts and minichloroplasts in Begoniaceae: iridescence and photosynthetic functioning - Shang-Hung Pao; Ping-Yun Tsai; Ching-I Peng; Pei-Ju Chen; Chi-Chu Tsai; En-Cheng Yang; Ming-Chih Shih; Jiannyeu Chen; Jun-Yi Yang; Peter Chesson; Chiou-Rong Sheue (Journal of Plant Research, 2018)

Differential Inhibition of Nav1.7 and Neuropathic Pain by Hybridoma-Produced and Recombinant Monoclonal Antibodies that Target Nav1.7 - Sangsu Bang; Jiho Yoo; Xingrui Gong; Di Liu; Qingjian Han; Xin Luo; Wonseok Chang; Gang Chen; Sang-Taek Im; Yong Ho Kim; Judith A. Strong; Ma-Zhong Zhang; et al. (Neuroscience Bulletin, 2018)

Arg913Gln of SLC12A3 gene promotes development and progression of end-stage renal disease in Chinese type 2 diabetes mellitus - Rong Zhang; Langen Zhuang; Ming Li; Juan zhang; Weijing Zhao; Xiaoxu Ge; Yating Chen; Feng Wang; Niansong Wang; Yuqian Bao; Limei Liu; Yanjun Liu; et al. (Molecular and Cellular Biochemistry, 2018)

Effects of potassium deficiency on root morphology, ultrastructure and antioxidant enzyme system in sweet potato (Ipomoea batatas [L.] Lam.) during early growth - Ming Liu; Ai-Jun Zhang; Xiao-Guang Chen; Rong Jin; Hong-Min Li; Zhong-Hou Tang (Acta Physiologiae Plantarum, 2017)

Development of a Time-Resolved Fluorescence Immunoassay for the Diagnosis of Hepatocellular Carcinoma Based on the Detection of Glypican-3 - Juan-Juan Chen; Chun-Mei Xie; Cong-Rong Wang; Yong Wan; Zhi-Ning Dong; Ming Li; Wei-Wen Xu (Journal of Fluorescence, 2017)

MEF2D Mediates the Neuroprotective Effect of Methylene Blue Against Glutamate-Induced Oxidative Damage in HT22 Hippocampal Cells - Zi-wei Chen; Anmin Liu; Qingyu Liu; Jingkao Chen; Wen-ming Li; Xiao-juan Chao; Qian Yang; Pei-qing Liu; Zi-xu Mao; Rong-biao Pi (Molecular Neurobiology, 2017)

Changes and relations of photosynthesis and iron cycling in anoxic paddy soil amended with high concentrations of sulfate - Qin Chen; Rong Jia; Dong Qu; Ming Li (Environmental Science and Pollution Research, 2017)

One-step reverse transcription loop-mediated isothermal amplification assay for rapid detection of melon yellow spot virus - Rong Zeng; Li-hui Xu; Shi-gang Gao; Xiu-hong Ni; Chun-lei Chen; Jian-cai Chen; Fu-ming Dai (European Journal of Plant Pathology, 2016)

Genetic Diversity and Population Structure Patterns in Chinese Cherry (Prunus pseudocerasus Lindl) Landraces - Tao Chen; Xiao-jiao Huang; Jing Zhang; Qing Chen; Yin Liu; Hao-ru Tang; Dong-ming Pan; Xiao-rong Wang (Plant Molecular Biology Reporter, 2016)

Erratum to: An Up-regulation of IRF-1 After a Spinal Cord Injury: Implications for Neuronal Apoptosis - Jian Zhao; Chen Chen; Jian-Ru Xiao; Hai-Feng Wei; Xu-hui Zhou; Xing-Xing Mao; Wei-dong Zhang; Rong Qian; Xin-lei Chen; Ming-qing He; Xiao-Wei Yu; Jian Zhao (Journal of Molecular Neuroscience, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Lentibacillus amyloliquefaciens sp. nov., a halophilic bacterium isolated from saline sediment sample - Jing-Li Wang; Ke-Dong Ma; Yan-Wei Wang; Hui-Min Wang; Yan-Bin Li; Shan Zhou; Xiao-Rong Chen; De-Long Kong; Xiang Guo; Ming-Xiong He; Zhi-Yong Ruan (Antonie van Leeuwenhoek, 2016)

An Up-regulation of IRF-1 After a Spinal Cord Injury: Implications for Neuronal Apoptosis - Jian Zhao; Chen Chen; Jian-Ru Xiao; Hai-Feng Wei; Xu-hui Zhou; Xing-Xing Mao; Wei-dong Zhang; Rong Qian; Xin-lei Chen; Ming-qing He; Xiao-Wei Yu; Jian Zhao (Journal of Molecular Neuroscience, 2015)
IRF-1, a kind of transcription factor, is expressed in many cell types, except in early embryonal cells. IRF-1 has played an essential role in various physiological and pathological processes, including tumor immune surveillance, viral infection, development of immunity system and pro-inflammatory injury. However, the expression and function of IRF-1 in spinal cord injury (SCI) are still unknown. In this study, we have performed an acute SCI model in adult rats and investigated the dynamic changes of IRF-1 expression in the spinal cord. Western blot have shown that IRF-1 protein levels gradually increased, reaching a peak at day 3 and then gradually declined to a normal level at day 14 after SCI. Double immunofluorescence staining showed that IRF-1 immunoreactivity was found in neurons, but not in astrocytes and microglia. Additionally, colocalization of IRF-1/active caspase-3 was detected in neurons. In vitro, IRF-1 depletion, by short interfering RNA, obviously decreases neuronal apoptosis. In conclusion, this is the first description of IRF-1 expression in spinal cord injury. Our results suggested that IRF-1 might play crucial roles in CNS pathophysiology after SCI.

Spiculisporic acid analogues of the marine-derived fungus, Aspergillus candidus strain HDf2, and their antibacterial activity - Rong Wang; Zhi Kai Guo; Xiang Min Li; Fu Xiao Chen; Xia Fei Zhan; Ming Hui Shen (Antonie van Leeuwenhoek, 2015)

Flavobacterium shanxiense sp. nov., Isolated from Soil - Fan Yang; Hong-ming Liu; Rong Zhang; Ding-bin Chen; Xiang Wang; Xin Yan; Qing Hong; Shun-peng Li (Current Microbiology, 2015)

Paenibacillus vini sp. nov., isolated from alcohol fermentation pit mud in Sichuan Province, China - Xiao-Rong Chen; Cheng-Bin Shao; Yan-Wei Wang; Ming-Xiong He; Ke-Dong Ma; Hui-Min Wang; De-Long Kong; Xiang Guo; Yi-Qing Zhou; Zhi-Yong Ruan (Antonie van Leeuwenhoek, 2015)

Rapid detection of copper chlorophyll in vegetable oils based on surface-enhanced Raman spectroscopy - Wei-Nan Lian; Jessie Shiue; Huai-Hsien Wang; Wei-Chen Hong; Po-Han Shih; Chao-Kai Hsu; Ching-Yi Huang; Cheng-Rong Hsing; Ching-Ming Wei; Juen-Kai Wang; Yuh-Lin Wang (Food Additives & Contaminants: Part A, 2015)

Transformation of the endophytic fungus Acremonium implicatum with GFP and evaluation of its biocontrol effect against Meloidogyne incognita - Yu-Rong Yao; Xue-Liang Tian; Bao-Ming Shen; Zhen-Chuan Mao; Guo-hua Chen; Bing-Yan Xie (World Journal of Microbiology and Biotechnology, 2015)

The Marginal Division of the Striatum and Hippocampus Has Different Role and Mechanism in Learning and Memory - Si-Yun Shu; Gang Jiang; Qi-Yi Zeng; Bin Wang; Hong Li; Lin Ma; Harry Steinbusch; Cai Song; Wood-Yee Chan; Xu-Hong Chen; Yon-Ming Wu; Rong Bao; et al. (Molecular Neurobiology, 2015)

Increased prevalence of hepatitis C virus subtype 6a in China: a comparison between 2004–2007 and 2008–2011 - Xia Rong; Ru Xu; Huaping Xiong; Min Wang; Ke Huang; Qiuyu Chen; Chengyao Li; Qiao Liao; Jieting Huang; Wenjie Xia; Guangping Luo; Xin Ye; et al. (Archives of Virology, 2014)

Retraction Note to: Characterization of cancer stem-like cells in the side population cells of human gastric cancer cell line MKN-45 - Hai-hong Zhang; Ai-zhen Cai; Xue-ming Wei; Li Ding; Feng-zhi Li; Ai-ming Zheng; Da-jiang Dai; Rong-rong Huang; Hou-jun Cao; Hai-yang Zhou; Jian-mei Wang; Xue-jing Wang; et al. (Journal of Zhejiang University-SCIENCE B, 2014)

Analysis on the association between PPARα/γ polymorphisms and lipoprotein(a) in a Chinese Han population - Hui-Jian Xie; Bo Hai; Ming Wu; Qiu Chen; Meng-Meng Liu; Chen Dong; Zhi-Rong Guo (Molecular Genetics and Genomics, 2014)

Analyzing and modeling rheological behavior of liver fibrosis in rats using shear viscoelastic moduli - Ying Zhu; Yi Zheng; Yuan-yuan Shen; Xin Chen; Xin-yu Zhang; Hao-ming Lin; Yan-rong Guo; Tian-fu Wang; Si-ping Chen (Journal of Zhejiang University-SCIENCE B, 2014)

Functional Investigation of Transmembrane Helix 3 in H+-Translocating Pyrophosphatase - Ching-Hung Lee; Yen-Wei Chen; Yun-Tzu Huang; Yih-Jiuan Pan; Chien-Hsien Lee; Shih-Ming Lin; Lin-Kun Huang; Yueh-Yu Lo; Yu-Fen Huang; Yu-Di Hsu; Shih-Chung Yen; Jenn-Kang Hwang; et al. (The Journal of Membrane Biology, 2013)

Enhancing production of a 24-membered ring macrolide compound by a marine bacterium using response surface methodology - Hua Chen; Mian-bin Wu; Zheng-jie Chen; Ming-lu Wang; Jian-ping Lin; Li-rong Yang (Journal of Zhejiang University-SCIENCE B, 2013)

RETRACTED ARTICLE: Characterization of cancer stem-like cells in the side population cells of human gastric cancer cell line MKN-45 - Hai-hong Zhang; Ai-zhen Cai; Xue-ming Wei; Li Ding; Feng-zhi Li; Ai-ming Zheng; Da-jiang Dai; Rong-rong Huang; Hou-jun Cao; Hai-yang Zhou; Jian-mei Wang; Xue-jing Wang; et al. (Journal of Zhejiang University-SCIENCE B, 2013)

MicroRNA profiles and their control of male gametophyte development in rice - Hua Peng; Jun Chun; Tao-bo Ai; Yong-ao Tong; Rong Zhang; Ming-ming Zhao; Fang Chen; Sheng-hua Wang (Plant Molecular Biology, 2012)

N-(1-Pyrenyl) maleimide inhibits telomerase activity in a cell free system and induces apoptosis in Jurkat cells - Pei-Rong Huang; Yuan-Ming Yeh; Chia-Chu Pao; Chi-Yuan Chen; Tzu-Chien V. Wang (Molecular Biology Reports, 2012)

Tryptophan decarboxylase plays an important role in ajmalicine biosynthesis in Rauvolfia verticillata - Wanhong Liu; Rong Chen; Min Chen; Haoxing Zhang; Meifang Peng; Chunxian Yang; Xingjia Ming; Xiaozhong Lan; Zhihua Liao (Planta, 2012)

Genetic diversity analysis of Rhododendron aureum Georgi (Ericaceae) located on Changbai Mountain using ISSR and RAPD markers - Yan-Fei Liu; Ming Xing; Wei Zhao; Rong-Jun Fan; Su Luo; Xia Chen (Plant Systematics and Evolution, 2012)

An antifungal compound from Trichoderma harzianum SQR-T037 effectively controls Fusarium wilt of cucumber in continuously cropped soil - Li-Hua Chen; Ya-Qing Cui; Xing-Ming Yang; Di-Kun Zhao; Qi-Rong Shen (Australasian Plant Pathology, 2012)

Comparison of Bacterial and Fungal Communities Between Natural and Planted Pine Forests in Subtropical China - Ming Nie; Han Meng; Ke Li; Jia-Rong Wan; Zhe-Xue Quan; Chang-Ming Fang; Jia-Kuan Chen; Bo Li (Current Microbiology, 2012)

Increased production of succinic acid in Escherichia coli by overexpression of malate dehydrogenase - Li-ya Liang; Rong-ming Liu; Jiang-feng Ma; Ke-quan Chen; Min Jiang; Ping Wei (Biotechnology Letters, 2011)

Spartina alterniflora invasion increases soil inorganic nitrogen pools through interactions with tidal subsidies in the Yangtze Estuary, China - Rong Hao Peng; Chang Ming Fang; Bo Li; Jia Kuan Chen (Oecologia, 2011)

Cytosolic PrP Induces Apoptosis of Cell by Disrupting Microtubule Assembly - Xiao-Li Li; Gui-Rong Wang; Yuan-Yuan Jing; Ming-Ming Pan; Chen-Fang Dong; Rui-Min Zhou; Zhao-Yun Wang; Qi Shi; Chen Gao; Xiao-Ping Dong (Journal of Molecular Neuroscience, 2011)

Green tea extract given before regional myocardial ischemia–reperfusion in rats improves myocardial contractility by attenuating calcium overload - Ying-Ming Liou; Shih-Rong Hsieh; Tsu-Juey Wu; Jan-Yow Chen (Pflügers Archiv - European Journal of Physiology, 2010)

The phylogeny analysis of MyoG gene in different pig breeds - Li Zhu; Xue-Wei Li; Su-Rong Shuai; Ming-Zhou Li; Lei Chen; Yi-Ren Gu; Kai Zhang (Interdisciplinary Sciences: Computational Life Sciences, 2010)

Green tea extract protects rats against myocardial infarction associated with left anterior descending coronary artery ligation - Shih-Rong Hsieh; Dan-Chin Tsai; Jan-Yow Chen; Sen-Wei Tsai; Ying-Ming Liou (Pflügers Archiv - European Journal of Physiology, 2009)

Chemical constituents from the leaves of Machilus zuihoensis Hayata var. mushaensis (Lu) Y.C. Liu - Chung-Yi Chen; Ming-Jen Cheng; Yi-Jung Chiang; Jia-Chi Bai; Chih-Tsao Chiu; Rong-Jyh Lin; Yen-Ray Hsui; Wen-Li Lo (Natural Product Research, 2009)

Holocene vegetation history with implications of human impact in the Lake Chaohu area, Anhui Province, East China - Wei Chen; Wei-Ming Wang; Xue-Rong Dai (Vegetation History and Archaeobotany, 2009)

TRANSPARENT TESTA 12 genes from Brassica napus and parental species: cloning, evolution, and differential involvement in yellow seed trait - You-Rong Chai; Bo Lei; Hua-Lei Huang; Jia-Na Li; Jia-Ming Yin; Zhang-Lin Tang; Rui Wang; Li Chen (Molecular Genetics and Genomics, 2009)

Development of the male reproductive structures in Taxus yunnanensis - Bing-Yi Wang; Jian-Rong Su; Danilo D. Fernando; Zong-Hui Yang; Zhi-Jun Zhang; Xiao-Ming Chen; Yan-Ping Zhang (Plant Systematics and Evolution, 2008)

Different expression patterns of CK2 subunits in the brains of experimental animals and patients with transmissible spongiform encephalopathies - Jian-Ming Chen; Chen Gao; Qi Shi; Bing Shan; Yan-Jun Lei; Chen-Fang Dong; Run An; Gui-Rong Wang; Bao-Yun Zhang; Jun Han; Xiao-Ping Dong (Archives of Virology, 2008)

A new dibenzofuran and other constituents from Ligularia caloxantha , a chinese medicinal plant - Shu-Yun Shi; Ming-Hui Hu; Di-Yao Wu; Chang-Xin Zhou; Jian-Xia Mo; Juan-Hua Xu; Liu-Rong Chen; Hui Dou; Hua Peng; Xiao-Jiang Hao; Joachim Stöckigt; Yu Zhao (Natural Product Research, 2008)

Induction of apoptosis in rabbit oral mucosa by 1.23% acidulated phosphate fluoride gel - Chia-Ling Tsai; Jui-Wei Lin; Hsi-Kung Kuo; Ming-Hong Tai; Yi-Chen Wu; Chih-Rong Shyr; Pei-Chang Wu (Archives of Toxicology, 2008)

Protection against hydrogen peroxide-induced injury by Z-ligustilide in PC12 cells - Yan Yu; Jun-Rong Du; Chen-Yuan Wang; Zhong-Ming Qian (Experimental Brain Research, 2008)

Proteomic profiling of proteins dysregulted in Chinese esophageal squamous cell carcinoma - Xiao-Li Du; Hai Hu; De-Chen Lin; Shu-Hua Xia; Xiao-Ming Shen; Yu Zhang; Man-Li Luo; Yan-Bin Feng; Yan Cai; Xin Xu; Ya-Ling Han; Qi-Min Zhan; et al. (Journal of Molecular Medicine, 2007)

Silver nanoparticles: partial oxidation and antibacterial activities - Chun-Nam Lok; Chi-Ming Ho; Rong Chen; Qing-Yu He; Wing-Yiu Yu; Hongzhe Sun; Paul Kwong-Hang Tam; Jen-Fu Chiu; Chi-Ming Che (JBIC Journal of Biological Inorganic Chemistry, 2007)

Roots of pioneer trees in the lower sub-tropical area of Dinghushan, Guangdong, China - Yan-ru Hao; Shao-lin Peng; Jiang-ming Mo; Xin-wei Liu; Zhuo-quan Chen; Kai Zhou; Jin-rong Wu (Journal of Zhejiang University-SCIENCE B, 2006)

Inferring population history from fine‐scale spatial genetic analysis in Oryza rufipogon (Poaceae) - XIAN XU; BAO‐RONG LU; YOLANDA H. CHEN; MING XU; JUN RONG; PINGYANG YE; JIAKUAN CHEN; ZHIPING SONG (Molecular Ecology, 2006)
Determining the genetic structure of an in situ conserved population can provide insight into the dynamics of population genetic processes associated with successful plant conservation. We used 21 microsatellite loci to analyse the genetic relationships among individuals ( n = 813) collected from a small Oryza rufipogon population conserved since 1993 in Hunan Province of China. The analysis revealed four distinct genetic subpopulations ( F ST = 0.145) without geographic isolation. One subpopulation was composed of possible introgressed individuals, two subpopulations were composed of seed recruits and their descendants, and the fourth subpopulation consisted of reintroduced individuals, seed recruits and their descendants. Positive spatial genetic structures were detected by spatial autocorrelation statistics at the population ( c . 63 m) and subpopulation levels (11–30 m), but the degree of autocorrelation was stronger at the population level. These results showed that prejudging the cryptic structure is important before autocorrelation analysis for the entire population. Our study suggests that population history can be a significant determinant on population structure for plant restoration projects.

FPF1 transgene leads to altered flowering time and root development in rice - Ming-Li Xu; Jia-Fu Jiang; Lei Ge; Yun-Yuan Xu; Hui Chen; Yuan Zhao; Yu-Rong Bi; Jiang-Qi Wen; Kang Chong (Plant Cell Reports, 2005)